Affluent Effluent: Visualizing the invisible during the development of an algal bloom using systems dynamics modelling and augmented reality technology. (January 2022) - Bryceson, Kim P.; Leigh, Steve; Sarwar, Salman; Grøndahl, Lisbeth
Abstract: Eutrophication causes structural changes to the ecosystem of a water body such as increased production of algae and aquatic plants, depletion of fish species, and a general deterioration of water quality. We discuss the development of an Augmented Reality (AR) application (App) based on a generalised system dynamics model of chemical and biological processes involved in the development of algal blooms. The objective was to generate user-based decision-making scenarios that could be visualised in real-time 'to see what cannot be seen in real life', for agricultural and environmental management training. Visualisation of the modelled processes is an important part of enhancing learning outcomes. This was achieved by transposing the system dynamics (SD) model into C# and the game engine Unity for the development of a hands-on learning environment through an AR App called Affluent Effluent on the Microsoft platform 'Hololens'. Conceptual and technological challenges and solutions associated with the App development are discussed, as is a brief evaluation. Highlights: Development and delivery of Augmented Reality App 'Affluent Effluent'. App enables user-based decision-making scenarios in wastewater management visualised in real time. Aim to 'see what cannot be seen in real life' for agricultural and environmental management training. Combined use of systems dynamics modelling and augmented reality technology. Challenges and solutions discussed for delivering an immersive environment of a complex system.